Opioid use and patient outcomes in an Australian hip and knee arthroplasty cohort. Issue 9 (8th August 2022) - Huang, Phil; Brownrigg, Jack; Roe, Justin; Carmody, David; Pinczewski, Leo; Gooden, Benjamin; Lyons, Matthew; Salmon, Lucy; Martina, Ka; Crighton, Joanna; O'Sullivan, Michael
Abstract: Background: To determine the prevalence of opioid use in Australian hip (THA) or knee (TKA) cohort, and its association with outcomes. Methods: About 837 primary THA or TKA subjects prospectively completed Oxford Scores, and Knee or Hip Osteoarthritis Outcomes Score(KOOS/HOOS) and opioid use in the previous week before arthroplasty. Subjects repeated the baseline survey at 6 months, with additional questions regarding satisfaction. Results: Opioid use was reported by 19% preoperatively and 7% at 6 months. Opioid use was 46% at 6 weeks and 10% at 6 months after TKR, and 16% at 6 weeks and 4% at 6 months after THR. Preoperative opioid use was associated with back pain(OR 2.2, P  = 0.006), anxiety or depression(OR 1.8, P  = 0.001) and Oxford knee scores <30(OR 5.6, P  = 0.021) in TKA subjects, and females in THA subjects(OR 1.7, P  = 0.04). There was no difference between preoperative opioid users and non‐users for satisfaction, or KOOS or HOOS scores at 6 months. 77% of patients taking opioids before surgery had ceased by 6 months, and 3% of preoperative non users reported opioid use at 6 months. Opioid use at 6 months was associated with preoperative use (OR 6.6–14.7, P  < 0.001), and lower 6 month oxford scores (OR 4.4–83.6, P  < 0.01). Conclusion: One in five used opioids before arthroplasty. Pre‐operative opioid use was the strongest risk factor for opioid use at 6 months, increasing odds 7–15 times. Prolonged opioid use was rarely observed in the opioid naïve (<5% TKA and 1% THA). Preoperative opioid use was not associated with inferior outcomes or satisfaction. Abstract : In this Australian privately insured cohort opioid use was reported by 19% preoperatively and 7% at 6 months. Pre‐operative opioid use was the strongest risk factor for opioid use at 6 months, increasing the odds 7–15 times. Preoperative opioid use was not associated with inferior outcomes or satisfaction.